High-sensitivity visualization of localized electric fields using low-energy electron beam deflection. (8th May 2018) - Jeong, Samuel; Ito, Yoshikazu; Edwards, Gary; Fujita, Jun-ichi
Abstract: The visualization of localized electronic charges on nanocatalysts is expected to yield fundamental information about catalytic reaction mechanisms. We have developed a high-sensitivity detection technique for the visualization of localized charges on a catalyst and their corresponding electric field distribution, using a low-energy beam of 1 to 5 keV electrons and a high-sensitivity scanning transmission electron microscope (STEM) detector. The highest sensitivity for visualizing a localized electric field was ∼0.08 V/µm at a distance of ∼17 µm from a localized charge at 1 keV of the primary electron energy, and a weak local electric field produced by 200 electrons accumulated on the carbon nanotube (CNT) apex can be visualized. We also observed that Au nanoparticles distributed on a CNT forest tended to accumulate a certain amount of charges, about 150 electrons, at a −2 V bias.